Ictal infraslow activity in stereoelectroencephalography: Beyond the "DC shift". Issue 1 (January 2016) - Thompson, S.A.; Krishnan, B.; Gonzalez-Martinez, J.; Bulacio, J.; Jehi, L.; Mosher, J.; Alexopoulos, A.; Burgess, R.C.
Highlights: We demonstrate that seizures possess an infraslow spatiotemporal signature, with biphasic peaks in power at ictal onset and offset. Our data argue that infraslow activity arises from a network process, as a component of ictal wideband dynamics. These findings provide advances in the understanding of the epileptogenic zone in stereoelectroencephalography. Abstract: Objectives: The significance of infraslow activity (ISA) in focal epilepsies is largely unknown. Recent work has demonstrated ictal ISA to be more widespread in expression than originally understood. Analysis of ISA by stereoelectroencephalography (SEEG) may help to clarify its localizing value, namely the focal versus widespread expression of ISA. Methods: The ictal SEEG records for fifteen consecutive adult patients were retrospectively analyzed, using both conventional (1.6–70 Hz) and infraslow (0.01–0.1 Hz) bandpass filters. When justified, seizures were averaged in the infraslow band to clarify their stereotypy. Wavelets were used to quantify the time–frequency characteristics of ISA. Results: All clinical seizures were found to possess ISA, and this was markedly invariant across seizures in a given patient. ISA showed biphasic peaks in power, both at ictal onset and offset, with this most prominent in the anatomical structures implicated by conventional analysis. In addition, ISA demonstrated an association with low voltage fast activity, and possessed a more restricted field than conventional activity. Conclusions: ISA is both widespread (anatomically distributed) and focal (closed electric field). Seizures possess an infraslow spatiotemporal signature. Significance: Beyond representing a "focus" of paroxysmal activity, ISA must arise from a network process as a component of wideband ictal dynamics. How this relates to clinical definition of the epileptogenic zone requires further study.